A new cosmic ray observation at Syowa Station in the antarctic - Kato, Chihiro; Kihara, Wataru; Ko, Yukino; Munakata, Kazuoki; Uchida, Shin-ichi; Kaimi, Sou; Kataoka, Ryuho; Kadokura, Akira; Evenson, Paul; Nakamura, Yoshiaki; Murase, Kiyoka; Miyake, Shoko (2021)
A set of Cosmic Ray detectors was newly installed in Syowa Station, in the Antarctic, to observe CR neutrons and muons simultaneously at the same location. The observing system has started working in February 2018 and is in stable operation with a high operation rate, >90%. We describe the new systems and show its stability.